A Low Complexity Navigation Data Estimation Algorithm for Weak GNSS Signal Tracking - Shunxiao Wu; Yangbo Huang; Shaojie Ni; Gang Ou (Universitas Ahmad Dahlan, 2015)
The computation load of traditional navigation data estimation algorithms for weak GNSS signal tracking increases exponentially with respect to the number of data bits needed to be estimated. To solve this problem, by adopting the dynamic programming philosophy, a navigation data bits estimation algorithm is proposed. The proposed algorithm uses the partial sum of correlation values as data bit combination searching branches. It can predict and exclude searching branches of data bit combination which have small coherent accumulated energy as soon as possible by angle quantification, thus reducing its computation load to be linearly related to the number of data bits needed to be estimated. Simulation results show that for signal of 500bps navigation data rate, the carrier track loop with a frequency discriminator implementing 0.12s coherent accumulation by navigation data estimation improves the tracking sensitivity up to 7 dB compared with traditional frequency discriminator under the same track accuracy constraint.